C S F pseudocysts peritoneal cavity following V P shunt surgery: Report of three cases in children and review of literature - Ghritlaharey Rajendra; Budhwani K; Shrivastava D; Jain A; Gupta G; Kushwaha A (Wolters Kluwer Medknow Publications, 2006)
Abdominal cerebrospinal fluid (CSF) pseudocyst is an uncommon complication following ventriculo-peritoneal (VP) shunt. The following report′s our experience with three cases of CSF pseudocyst in children. VP shunt was done earlier for communicating hydrocephalus following tubercular meningitis (TBM) in all cases. Clinical presentation was with progressive abdominal distension and features of intestinal obstruction. Clinically we were able to diagnose all cases as CSF pseudocyst peritoneal cavity. Ultrasound examination confirmed the clinical findings in all. CT scan of abdomen and pelvis showed a large unilocular CSF pseudocyst with shunt catheter within it on one patient (case 3). Ultrasound guided aspiration of cyst was done in case 1 alone, but failed to resolve the symptoms. All patients needed formal exploration. Near total cyst excision, adhesiolysis and relocation of peritoneal end of VP shunt catheter in right supra hepatic space was done in all. Two patients who developed shunt tract infection needed shunt removal. The follow up period is 6-8 months.